Development of preformulated products based on Nomuraea rileyi for control of Spodoptera frugiperda (Lepidoptera: Noctuidae) - VILLAMIZAR, LAURA; ARRIERO, CAROLINA; BOSA-O., CARLOS FELIPE; COTES, ALBA MARINA (Revista Colombiana de Entomología, 2004)
Nomuraea rileyi is the microorganism that is most frequently found causing natural field epizootics of Spodoptera frugiperda larvae in different maize production zones of Colombia; however, in the national market there are no registered products based on this fungus. Therefore, the objectives of the present work were to develop a method of mass production and develop biopesticide prototypes with a strain of the fungus N. rileyi selected for its control activity on the fall armyworm. A system for mass production of conidia was initially standardized after evaluating different solid matrices such as rice, wheat bran and mijo grains, contained in both, high-density polyethylene bags and aluminum trays, supplemented with different organic nitrogen sources and inoculated with different inoculum types. Once the medium was selected where the greatest conidia production per gram of substrate was obtained, the conidia were separated and used as active starter for elaborating the biopesticide prototypes. In the system of mass production in bags, the highest sporulation took place when millo grains were used, inoculated with eight day old fragments of agar grown with the sporulated fungus, this being at 30 x 108 conidia.g·1. Two delivery systems were developed for the biopesticide, an emulsifying concentrate with a concentration of 1x1011 conidia.g' and a wettable powder with a concentration of 1X109 conidios.g' with germinations of 92 and 87%, respectively. The systems of mass production were efficient and economical for conidia production and the preformulations represent a promising alternative for the control of the fall armyworm in maize.